Comparing the impacts of community policing in the cities of Nagpur and Tirunelveli: An empirical study. (June 2015) - Thakre, Amit Gopal; Sivakumar, R; Jaishankar, K
Community policing is a philosophically right strategy, but as yet its feasibility remains to be adequately established through scientific procedures. Impact assessment of community policing is much needed in contemporary literature. This paper comparatively examines the community policing movement between Mitra Police (Nagpur) and Friends of Police (Tirunelveli) ('FOP'). The findings of this study will assist in identifying which of the two has a better strategy and the reason for this. The variables are divided into input, supervision and outcome categories. This comparative study examined 240 respondents taken through a purposive method to compare the outcome of Mitra Police and FOP using SPSS. Overall, the inputs made into FOP were comparatively better than those for Mitra Police, but it is still lacking on many fronts. Lack of proper supervision process is found to be a major downfall of Mitra Police in Nagpur. In both cities community policing fails to improve police image. This study indicates important variables that are having significant impact on community policing effectiveness, and policy makers should factor in these findings to further refine community policing strategy in their locality.